Community Engagement Experiences of Social Entrepreneurs in Rural Communities - Teng-Calleja, Mendiola (Archīum Ateneo, 2023)
Using the lens of interpretative phenomenological analysis, this study explored the community engagement experiences of six social entrepreneurs working with rural communities in the Philippines and how they made meaning of their community engagement experience. Data were gathered through semistructured interviews. The findings illustrate how engaging with rural communities through social entrepreneurship is a way for the entrepreneurs to help communities uplift their economic condition and to achieve other social goals such as improvement of the community’s quality of life and environmental sustainability. Social entrepreneurship was also a way to help empower communities as well as build their capabilities, shape positive values through culture building, and nurture relationships. Implications of the study to social enterprise research and policy, community engagement programs, and leader development are discussed.